ROS-Mediated Signalling in Bacteria: Zinc-Containing Cys-X-X-Cys Redox Centres and Iron-Based Oxidative Stress. (29th September 2011) - Ortiz de Orué Lucana, Darío; Wedderhoff, Ina; Groves, Matthew R.
Abstract : Bacteria are permanently in contact with reactive oxygen species (ROS), both over the course of their life cycle as well that present in their environment. These species cause damage to proteins, lipids, and nucleotides, negatively impacting the organism. To detect these ROS molecules and to stimulate the expression of proteins involved in antioxidative stress response, bacteria use a number of different protein-based regulatory and sensory systems. ROS-based stress detection mechanisms induce posttranslational modifications, resulting in overall conformational and structural changes within sensory proteins. The subsequent structural rearrangements result in changes of protein activity, which lead to regulated and appropriate response on the transcriptional level. Many bacterial enzymes and regulatory proteins possess a conserved signature, the zinc-containing redox centre Cys-X-X-Cys in which a disulfide bridge is formed upon oxidative stress. Other metal-dependent oxidative modifications of amino acid side-chains (dityrosines, 2-oxo-histidines, or carbonylation) also modulate the activity of redox-sensitive proteins. Using molecular biology, biochemistry, biophysical, and structure biology tools, molecular mechanisms involved in sensing and response to oxidative stress have been elucidated in detail. In this review, we analyze some examples of bacterial redox-sensing proteins involved in antioxidative stress response and focus further on the currently known molecular mechanism of function.